Peningkatan Pemahaman Akidah Akhlak Siswa Kelas X Melalui Pemanfaatan Media Pembelajaran Digital Wordwall - Siti Lailatul Mubarokah; Ambarwati (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPROVING STUDENTS' UNDERSTANDING OF AKIDAH AKHLAK THROUGH WORDWALL DIGITAL LEARNING MEDIA The use of digital learning media has become an important strategy for improving the quality of instruction, particularly in Akidah Akhlak learning, which is often still dominated by conventional teaching methods. This study aimed to examine the effect of Wordwall as a digital learning medium on tenth-grade students’ understanding of Akidah Akhlak at MA Silahul Ulum Trangkil Pati. A quantitative approach was employed using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample involved 46 students, consisting of 22 students in the experimental class and 24 students in the control class. Data were collected through essay tests administered before and after the treatment and were analyzed using N-Gain, the Shapiro-Wilk normality test, and the Mann-Whitney U test. The results showed that the experimental class obtained an average N-Gain score of 42.87%, which was higher than the control class score of 23.86%. The Mann-Whitney U test produced a significance value of 0.000, which was below 0.05, indicating that Wordwall had a significant effect on students’ understanding. These findings suggest that Wordwall can serve as an interactive and engaging digital learning medium that enhances student participation and supports conceptual understanding in Akidah Akhlak learning.